The Semantic Figures Analysis, Meaning and Its Moral Value in The Poems of on the Pulse of Morning and Still I Rise by Maya Angelou - Muh. Al Fachrizah Fitra; Haryanto Atmowardoyo; Desy Satriyani Tamrin (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
A semantic figure is another term from figurative language which is the use of word that diverges from its normal meaning or a phrase that stylistic with a specialized meaning not based on the literal meaning of the words in it. The objectives of this study are examined two cases; (1) semantic figures in the poems of Maya Angelou; (2) moral value and its meaning of the poems. This study using descriptive qualitative method because post positivism form is used in this study. From this perspective, this study is seen as theoretical, in which results in a substantive formation based on conceptualizations on possible variation to compose, develop and reconstruct theory. There are two poems of Maya Angelou in this study as the samples; (1) On the Pulse of Morning; (2) Still I Rise. The results of this study indicated that there were many semantic figures implied. There were oppression and persecution meanings based on 2 poems. This study is proved that semantic figures and the meanings which are implied from 2 poems have important roles in convey moral value or message and idea to the reader and can be used as a guidance in our lives. The implication of this study is that the authors believe that this study is going to help the reader to understand what the semantic figures mean is, they also will know the meanings of the Maya Angelou’s poems collection.